2021
DOI: 10.3390/pharmaceutics13122107
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-Printed Polymer–Lipid-Hybrid Tablet towards the Development of Bespoke SMEDDS Formulations

Abstract: 3D printing is a rapidly growing area of interest within pharmaceutical science thanks to its versatility in creating different dose form geometries and drug doses to enable the personalisation of medicines. Research in this area has been dominated by polymer-based materials; however, for poorly water-soluble lipophilic drugs, lipid formulations present advantages in improving bioavailability. This study progresses the area of 3D-printed solid lipid formulations by providing a 3D-printed dissolvable polymer sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The drug release from 3D-printed SNEDDS tablets is influenced by several factors, such as the physical properties of drug SNEDDS and polymer SNEDDS, the microstructural properties and thickness of the HPC-Soluplus tablet shell, the properties of the dissolution medium (such as temperature and pH), and properties of the fluid/tablet wall (e.g., wettability/contact angle) [ 41 ]. Previous, studies have shown the incorporation of a solidified lipid matrix inside a 3D-printed system [ 42 ]. However, we expanded the scope of a multi-drug delivery regiment using a lipid-based formulation through our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug release from 3D-printed SNEDDS tablets is influenced by several factors, such as the physical properties of drug SNEDDS and polymer SNEDDS, the microstructural properties and thickness of the HPC-Soluplus tablet shell, the properties of the dissolution medium (such as temperature and pH), and properties of the fluid/tablet wall (e.g., wettability/contact angle) [ 41 ]. Previous, studies have shown the incorporation of a solidified lipid matrix inside a 3D-printed system [ 42 ]. However, we expanded the scope of a multi-drug delivery regiment using a lipid-based formulation through our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we expanded the scope of a multi-drug delivery regiment using a lipid-based formulation through our study. Semi-solid 3D printing of just lipid-based systems had poor printing fidelity and lacked consistency, which can be overcome by using the method employed in this study [ 24 , 26 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once all excipients and drugs were fully melted, they were transferred to a PAM cartridge for 3D printing. The dapagliflozin-loaded SNEDDS 3D-printed tablet showed an immediate release profile (>75% in 20 min) [ 142 ]. A similar approach was used to fabricate 3D-printed lidocaine-loaded SNEDDS suppositories to treat hemorrhoids by PAM [ 143 ].…”
Section: Implementation Of 3d Printing In Personalised Nanomedicinesmentioning
confidence: 99%
“…Furthermore, it demonstrates a 3D-printed biodegradable tablet to deliver bespoke and combined therapies in a single multi-compartment tablet. The versatility of these 3D-printed tablets has the potential to circumvent challenges associated with the adherence and safety of polypharmacy, together with the 3DP of lipophilic drugs [ 168 ]. Additionally, the study reports that the versatility of these 3D-printed tablets has the potential to circumvent challenges associated with the adherence and safety of polypharmacy, together with those related to the 3DP of lipophilic drugs.…”
Section: The 3d-printed Polymer–lipid Compositesmentioning
confidence: 99%